2019
DOI: 10.1111/jcmm.14567
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐transcriptome networks in whole blood and monocytes of women undergoing preterm labour

Abstract: Preterm birth is attributed to neonatal morbidity as well as cognitive and physiological challenges. We have previously identified significant differences in mRNA expression in whole blood and monocytes, as well as differences in miRNA concentration in blood plasma, extracellular vesicles (EV) and EV‐depleted plasma in women undergoing spontaneous preterm labour (sPTL). The goal of this analysis was to identify differences in miRNA expression within whole blood (WB) and peripheral monocytes (PM) from the same … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…One of the most striking pair was hsa-MORC3_0001-hsa-miR-1248-CHRM2. Hsa-miR-1248 was found significantly decreased in peripheral blood leukocytes of preterm women, and involved in the positive regulation of interleukin−2 signaling by binding to gene SASH3 and CD83 (Paquette et al, 2019). Interleukin−2, one of the proinflammatory factors mainly secreted by activated CD4 + Th1 cells, was reported to be elevated and stimulated the contraction of myometrium in PTB (Sykes et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…One of the most striking pair was hsa-MORC3_0001-hsa-miR-1248-CHRM2. Hsa-miR-1248 was found significantly decreased in peripheral blood leukocytes of preterm women, and involved in the positive regulation of interleukin−2 signaling by binding to gene SASH3 and CD83 (Paquette et al, 2019). Interleukin−2, one of the proinflammatory factors mainly secreted by activated CD4 + Th1 cells, was reported to be elevated and stimulated the contraction of myometrium in PTB (Sykes et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…This is a region of chromosome 14 which encodes 52 miRNAs. Some of them are produced by the placenta in substantial quantities and an enter maternal circulation [31]. C14MC is exclusively expressed from the maternal allele.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-200c-3p is downregulated at the first trimester in serum of pregnant women undergoing spontaneous abortion [36]. The level of miR-495-3p is deregulated in placenta from patients with preeclampsia and preterm labor [34], is decreased in the plasma and extracellular vesicles in second and third trimesters, but increased in the whole blood in the second trimester in women undergoing preterm labor [31,37]. Deregulated placental expression of miR-4494 is associated with preterm labor [38].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their non-invasive, convenient, and quantifiable attributes, circulating molecules are naturally promising biomarkers for non-invasive PTL prediction. 14,[63][64][65][66][67][68] An untargeted metabolomics profiling by Liang et al 69 found the metabolic clock of pregnancy based on the highly dynamic metabolic changes, in which 460 annotated compounds and 34 human metabolic pathways were significantly changed during healthy pregnancy. Based on their dynamic and precise change during pregnancy, with just three metabolites (THDOC, Androstane-3,17-diol, and Estriol-16-glucuronide), the metabolome accurately predicted an upcoming delivery event within 2 weeks with area under the receiver operating characteristic curve close to 0.9.…”
Section: Maternal Bloodmentioning
confidence: 99%
“…73 Comprehensive miRNA profiling of women undergoing sPTL in both whole blood and peripheral monocytes identifies a number of miRNAs (such as miR-495-3p and miR-381-3p in whole blood, miR-223 in plasma, and miR-1291-5p in monocytes) changes with sPTL, although they are limited to the small sample size to perform any predictive analyses. 68 In preterm pregnant women, cell-free circulating microparticles are also different from those in women undergoing term labor, which can be detected even in early pregnancy. Cantonwine et al 74 did proteomic analysis in circulating microparticles at 10-12 weeks gestation from term in labor and PTL women, and differentially expressed proteins were found in pathways related to coagulation, fibrinolysis, immune modulation, and the complement system.…”
Section: Maternal Bloodmentioning
confidence: 99%